Nurses’ knowledge and attitudes associated with nutrition education for malnutrition prevention in patients with chronic obstructive pulmonary disease - Erisca Carolina Tesalonike; Agung Waluyo; Denissa Faradita Aryani (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Malnutrition is one of the major complications among patients with chronic obstructive pulmonary disease (COPD) due to increased energy requirements and chronic systemic inflammation. This condition may worsen respiratory function, increase the risk of exacerbations, and reduce patients’ quality of life. Nutritional education plays an important role in preventing malnutrition; however, its implementation by nurses remains suboptimal. Purpose: To identify the relationship between nurses’ knowledge and attitudes and the implementation of nutritional education for malnutrition prevention among patients with COPD. Method: A cross-sectional study was conducted among 65 respondents providing nursing care to patients with COPD at Dr. H. Abdul Moeloek Regional General Hospital, Lampung, using a total sampling technique. Data were analyzed using Spearman’s correlation test and multiple linear regression. Results: There was a significant relationship between knowledge and the implementation of nutritional education (r=0.443, p<0.001), as well as between attitude and the implementation of nutritional education (r=0.718, p<0.001). No significant relationships were found between age, gender, educational level, length of employment, history of nutrition training, or experience in providing care for patients with COPD and the implementation of nutritional education (p>0.05). Attitude was identified as the variable most strongly associated with the implementation of nutritional education. Conclusions: Nurses’ knowledge and attitudes were significantly associated with the implementation of nutritional education as an effort to prevent malnutrition among patients with COPD. Attitude was the most dominant factor associated with the implementation of nutritional education.